2022
DOI: 10.1681/asn.2022020210
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Long-Lasting Regulatory B Lymphocytes by Modified Immune Cells in Kidney Transplant Recipients

Abstract: Background We recently demonstrated that donor-derived modified immune cells (MICs)—PBMCs that acquire immunosuppressive properties after a brief treatment— induced specific immunosuppression against the allogeneic donor when administered prior to kidney transplantation. We found an up to 68-fold increase in CD19+CD24hiCD38hi transitional B lymphocytes compared with transplanted controls. Methods Ten patients from a phase I clinical trial who had received MIC infusions before kidney transplantation were follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…The majority of Breg produced the immunosuppressive cytokine interleukin (IL) 10 3. Clinical and immunological findings in the 10 patients were stable with now more than 5 years of follow-up4 (unpublished results). In summary, MIC therapy was well tolerated in the phase I clinical trial and did not lead to humoral sensitisation or rejections.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The majority of Breg produced the immunosuppressive cytokine interleukin (IL) 10 3. Clinical and immunological findings in the 10 patients were stable with now more than 5 years of follow-up4 (unpublished results). In summary, MIC therapy was well tolerated in the phase I clinical trial and did not lead to humoral sensitisation or rejections.…”
Section: Introductionmentioning
confidence: 92%
“…We have recently shown that administration of modified immune cells (MIC) prior to kidney transplantation led to specific immunosuppression against the allogeneic donor, which may allow reduction of conventional immunosuppressive therapy 3 4. MIC are donor-derived peripheral blood mononuclear cells (PBMC) that are treated ex vivo by an alkylating agent.…”
Section: Introductionmentioning
confidence: 99%
“…In the current issue of JASN , Morath et al 5 take a step toward addressing this challenge in their report of 3-year clinical and immunologic outcomes for a group of ten living donor kidney transplant recipients who participated in a previously described phase 1 clinical trial of donor-derived modified immune cells (MICs). 2 The cell therapy for the trial consisted of donor-derived PBMCs (monocytes and lymphocytes) that were collected by leukapheresis, treated briefly with the cytotoxic agent mitomycin C, washed, resuspended in buffer, and administered directly to the transplant recipient as a single intravenous infusion either 2 or 7 days prior to transplantation.…”
mentioning
confidence: 99%
“…Tregs have also been proposed as a primary active mediator of immune regulation induced by tolerogenic cell therapies, including donor-derived apoptotic cells 12 and mesenchymal stromal cells. 3 Morath et al 5 analyzed the longitudinal Treg profiles of their trial participants, finding that, despite an early expansion of Tregs during the first post-transplant year, the longer-term proportions of the circulating level of Treg were rather low. It is possible, therefore, that an early interplay between Tregs and Bregs participates in the initial induction of donor-specific hyporesponsiveness following MIC administration.…”
mentioning
confidence: 99%
See 1 more Smart Citation